Magic and ritual in the ancient world - Mirecki, Paul Allan; Meyer, Marvin W. (Religions in the Graeco-Roman world, 2002)
This volume contains a series of essays that explore expressions of magic and ritual power in the ancient world. The essays are authored by scholars in the fields of Egyptology, ancient Near Eastern studies, the Hebrew Bible, Judaica, classical Greek and Roman studies, and Coptic and Islamic Egypt.